Ijtihad Muhammad Syahrur Dalam Upaya Pengembangan Epistimologi Hukum Islam Dan Implementasinya Dalam Bidang Ekonomi dan Keuangan Syariah - Azhari, Raihan Azmi; Muhajirin, Muhajirin (Universitas Islam Negeri Sumatera Utara, 2024)
Initially, in the early days of Islam, fiqh developed through ijtihad, namely the deductive process carried out by the scholars to find legal solutions in situations that had not been specifically regulated by the Al-Quran and Sunnah. However, along with the times, Muslim societies have faced significant social, economic and political changes. These changes encourage the expansion and increase in the complexity of Islamic law. The purpose of this research is to find out how Contemporary Islamic Law Theory and Systems Approach to legal theory and its implementation in the Field of Islamic Economics and Finance According to Muhammad Syahrur. The results of this study indicate that according to Syahrur, the laws that are applied in the reality of this world are relative and historical. His approach is based on common sense and objective reality. Syahrur replied that usury is only haram if there is an element of tyranny towards other parties, and bank interest is legal if the borrower is a businessman who is not entitled to receive zakat and alms in the modern world. The application of usury in the modern world is still being debated.